1979
DOI: 10.3406/bulmi.1979.7313
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon-rich fluid inclusions in minerals from the alkaline Ilímaussaq intrusion, South Greenland

Abstract: Les inclusions fluides des minéraux des syénites agpaïtiques à néphéline et des filons hydrothermaux de l'intrusion alcaline d'Ilímaussaq (Groenland du Sud) sont très riches en hydrocarbures (principalement en méthane) tandis que les pourcentages de CO2 et CO sont insignifiants. Les hydrocarbures sont considérés comme d'origine inorganique et comme reflétant des fugacités d'oxygène très basses pendant la cristallisation. Il est proposé que ces fluides ont été piégés comme des gouttelettes immiscibles dans une … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 0 publications
3
32
0
Order By: Relevance
“…Most work on the hydrocarbons in the Ilímaussaq intrusion has focused on gases in fluid inclusions, though the presence of discrete bitumen occurrences C 26 H 54 (named evenkite-like mineral) was mentioned by Konnerup-Madsen et al (1979). The stable carbon isotopic ratio of this material (d 13 C: À29&) clearly indicates a biogenic source, but the implication of this observation was not discussed by Konnerup-Madsen et al (1988).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Most work on the hydrocarbons in the Ilímaussaq intrusion has focused on gases in fluid inclusions, though the presence of discrete bitumen occurrences C 26 H 54 (named evenkite-like mineral) was mentioned by Konnerup-Madsen et al (1979). The stable carbon isotopic ratio of this material (d 13 C: À29&) clearly indicates a biogenic source, but the implication of this observation was not discussed by Konnerup-Madsen et al (1988).…”
Section: Introductionmentioning
confidence: 91%
“…More specific analyses on separate minerals revealed hydrocarbon gas concentrations up to more than 500 ppm of carbon in fluid inclusions (Konnerup-Madsen et al, 1979) and isotopic analysis on a large number of samples (d 13 C CH4 : À2 to À7&; d 13 C C2þ : À8 to À17&) also led Konnerup-Madsen et al (1988) to the conclusion that the gases were abiogenic in origin. Although different researchers agreed on the abiogenic nature of the gases, they had different views concerning their exact source; whether the hydrocarbons represented primary magmatic substance (Krumrei et al, 2007; or had formed via re-speciation of the magmatic gases carbon dioxide and water at lower temperatures, the solidus temperature of the Ilímaussaq magma, ca.…”
Section: Introductionmentioning
confidence: 95%
“…While the earliest descriptions of these Precambrian Shield-type gases date back to the 1880s, the first scientific papers to describe the phenomenon in Canada (Fritz et al, 1987;Sherwood Lollar et al, 1993a;Sherwood Lollar et al, 1993b), Finland (Nurmi and Kukkonen, 1986), the Kola Peninsula (Khitarov et al, 1979); and the Ilimaussaq complex in Greenland (Konnerup-Madsen et al,1979, 1988) largely focused on demonstrating that the majority of the gases were not consistent with known microbial or thermogenic gases and suggested a possible abiogenic origin in part by process of elimination. In contrast, the past several years have seen significant progress in understanding the controlling processes of gas formation in these environments, and the distribution of two major gas types.…”
Section: Introductionmentioning
confidence: 97%
“…Various fluid inclusion studies (Larsen, 1976;Konnerup-Madsen et al, 1979Konnerup-Madsen and Rose-Hansen, 1984;Konnerup-Madsen, 2001;Markl et al, 2001) showed that, with the exception of the alkali granite, primary fluid inclusions of the Ilímaussaq rocks are methane-dominated with lesser amounts of H 2 and higher hydrocarbons, but with only traces of H 2 O and CO 2 . Similar hydrocarbon-rich fluids have been described from other peralkaline complexes worldwide (e.g., Salvi and WilliamsJones, 1997;Potter et al, 1998).…”
mentioning
confidence: 98%
“…The fractionation trend found in the Ilímaussaq complex is governed by low activities of water and SiO 2 , which in turn are dependent on low oxygen fugacites in the parental melt. This results in highly reduced phase assemblages and in allowing the coexistence of two immiscible fluids (a methane-dominated gaseous and a highly saline aqueous fluid phase) during most of the crystallization history (Larsen, 1976;Konnerup-Madsen et al, 1979Konnerup-Madsen and Rose-Hansen, 1984;KonnerupMadsen, 2001;Markl et al, 2001a;Marks and Markl, 2001).…”
mentioning
confidence: 98%